PENGARUH TATA KELOLA PEMERINTAHAN, PENERIMAAAN PAJAK DAN EKSPOR TERHADAP PEREKONOMIAN DI ASIA PASIFIK - Mahriun, Dwi; Putri, Dewi Zaini (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study aims to examine the effect of governance , tax revenue and export on economy in Asia Pasific. The data used is panel data during the period 2010-2017, and collected by data documentation and library obtained from relevant institutions and agencies. The variables used are control of corruption (X1), political stability (X2), tax revenue (X3), expor (X4) and economy (Y). Using the panel data regression apporoach a sample of developed and developing countries, it finds: (i) control of corruption, tax revenue and export have a significant effect on economy, (ii) political stability have a insignificant effect on economy, (iii) and simultaneuosly all of the indenpendent variables in this study have a significant effect on economy.